2016
DOI: 10.1016/j.molcel.2016.03.011
|View full text |Cite
|
Sign up to set email alerts
|

S6K1 Phosphorylation of H2B Mediates EZH2 Trimethylation of H3: A Determinant of Early Adipogenesis

Abstract: SUMMARY S6K1 has been implicated in a number of key metabolic responses, which contribute to obesity. Critical among these is the control of a transcriptional program required for the commitment of mesenchymal stem cells to the adipocytic lineage. However, in contrast to its role in the cytosol, the functions and targets of nuclear S6K1 are unknown. Here, we show that adipogenic stimuli trigger nuclear translocation of S6K1, leading to H2BS36 phosphorylation and recruitment of EZH2 to H3, which mediates H3K27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(78 citation statements)
references
References 40 publications
3
74
1
Order By: Relevance
“…Consistently, the phosphorylation of S6, which is a downstream substrate of S6K1, was also higher in the βTC6 cells ( Figure 1D). In line with our previous work, 15 the global level of suppressing histone mark H3K27me3 was parallel to the level of active S6K1, while the active histone mark H3K4me3 showed the opposite tendency ( Figure 1D). As shown in Figure 1, S6K1 exhibited increased activation in β cells, and impaired S6K1 signaling was associated with an increase in the genetic identity of α cells.…”
Section: Involvement Of S6k1 In Pancreatic α/β Cell Identitysupporting
confidence: 92%
“…Consistently, the phosphorylation of S6, which is a downstream substrate of S6K1, was also higher in the βTC6 cells ( Figure 1D). In line with our previous work, 15 the global level of suppressing histone mark H3K27me3 was parallel to the level of active S6K1, while the active histone mark H3K4me3 showed the opposite tendency ( Figure 1D). As shown in Figure 1, S6K1 exhibited increased activation in β cells, and impaired S6K1 signaling was associated with an increase in the genetic identity of α cells.…”
Section: Involvement Of S6k1 In Pancreatic α/β Cell Identitysupporting
confidence: 92%
“…Inhibition of mTORC1 by either rapamycin treatment or an adipose-specific knockout of regulatory-associated protein of mTOR (also known as RPTOR or raptor, a major component of mTORC1), inhibits adipogenesis1114. Conversely, activation of mTORC1 enhances adipogenesis by increasing PPARγ13, confirming a positive role for mTOR in adipogenesis15. Despite this, mTOR also maintains homeostasis of adipogenesis by suppressing the expression of PPARγ through insulin receptor substrate-1 (IRS-1)/Akt signaling1617, suggesting an indispensable function for mTOR in adipogenesis.…”
mentioning
confidence: 95%
“…This phosphorylation mark directly promotes the transcription of response genes needed to handle metabolic stress. Other papers report the direct phosphorylation of Ser 36 on H2B by S6K1 (40), which is also a player in the LKB1-AMPK-mTORC1 signaling axis, with S6K1 being phosphorylated by mTORC1. mTORC1 is another player in the epigenetic response to nutrient sensing.…”
Section: Heritable Epigenetic Modifications Acquired Through Microenvmentioning
confidence: 99%
“…Epigenetic marks induced by nutrient sensing proteins and complexes have the ability to greatly alter cellular metabolism, making a useful feed-forward mechanism for acclimation and adaptation to the current metabolic microenvironment. The phosphorylation of Ser 36 on Histone 2B is a significant epigenetic mark made by two proteins involved in nutrient sensing: AMPK and S6K1 (39,40). It has been shown that phosphorylation of Ser 36 on Histone 2B is significantly increased upon treatment of cells with 2-Deoxy Glucose (39), which mimics a glucose deprived environment.…”
Section: Effect Of Heritable Epigenetic Modifications On Tumor Metabomentioning
confidence: 99%
See 1 more Smart Citation